Ontogenetic Base for the Shape Variation of Flowers in Malesherbia Ruiz & Pav. (Passifloraceae) - Bull-Hereñu, Kester; Ronse De Craene, Louis P. (Frontiers in Ecology and Evolution, 2020)
The flower of Malesherbia Ruiz & Pav. (Passifloraceae) is a suitable model to study how far growth constraints throughout ontogeny are causal for the variation in the proportions of reproductive structures. The Malesherbia flower is characterized by a marked hypanthium subtending five alternating sepal and petal lobes plus a coronal rim. In Malesherbia, the size relation between hypanthial tube and perianth lobes conditions the general aspect that the flower of a given species may display. For instance, flowers of taxa belonging to the section Malesherbia are characterized by a predominant hypanthium much similar to tubular flowers with reduced erect perianth lobes and a protruding paracorollar cylinder, while the opposite is true for the remaining species of the genus resembling a radiate ten-parted open flower with a reduced corona. Further morphological variation in the genus includes the bimodal distribution of absolute size of the mature flower, with some species showing much smaller dimensions (e.g. M. humilis) and also the variability in the level of aggregation of the inflorescences ranging from uniflorous (M. lactea), through racemose (M. densiflora, M. lirana) up to very condensed and globular in shape (M. fasciculata). In this work we studied under SEM the flower morphogenesis of 14 Malesherbia species collected in the Andean and desertic region of septentrional Chile. Against expectations, our data showed that the growth of petal lobe primordia is relatively faster in tubular flowers than in radiate ones, despite the latter presence of a much showier perianth at maturity. Absolute flower size could also be related to absolute meristem size and a relative developmental arrest was detected in the flower buds of very condensed inflorescences. Our results support the idea of a common constraint throughout ontogeny in which earlier inception and faster organ growth leads to relatively smaller dimensions coupled with earlier maturation and arrest of elongation.